PENGELOLAAN KELAS ANAK USIA DINI BERBASIS PENDEKATAKAN PERSAUDARAAN DALAM PENDIDIKAN AGAMA ISLAM - Nina Amelia; Irawan; Erni Haryanti (Program Studi Manajemen Pendidikan, 2025)
Abstract: This study aims to describe the concept and implementation of classroom management based on brotherhood (ukhuwah) in Islamic Religious Education (IRE) for early childhood. This approach emerges from the need for a learning model that is more humanistic, participatory, and relevant to Islamic values. The method employed is descriptive qualitative research based on a literature study, using content analysis of various sources related to classroom management, the values of ukhuwah Islamiyah, humanistic education, and student-centered learning approaches.The findings indicate that brotherhood-based classroom management emphasizes the creation of harmonious, respectful, and collaborative interactions between teachers and students as well as among students. The values of ukhuwah serve as a foundation for building a safe and inclusive learning environment that encourages active participation among children. The implementation of this approach is realized through the use of humanistic learning methods, cooperative learning, collaborative learning, inquiry-based learning, and project-based learning, which have been shown to enhance students’ cognitive, emotional, social, and moral development. Furthermore, classroom management grounded in the values of brotherhood strengthens the formation of Islamic character traits such as empathy, cooperation, and care for others. Therefore, this model can serve as a strategic alternative for improving the quality of Islamic Religious Education for early childhood in a more effective and meaningful manner. Keywords: Islamic Education; Early Childhood Education; Class Management